Pelaksanaan Akad Musyarakah dalam Perbankan Syariah - Rifdah Atika Pasaribu; Tuti Anggraini MA (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This research examines the implementation of musyarakah contracts in the Islamic banking system in Indonesia. The main focus of the study is to analyze the implementation mechanisms, challenges faced, and development strategies of musyarakah contracts. Using a qualitative approach with a descriptive-analytical method, this research combines primary data from in-depth interviews with Islamic banking practitioners and secondary data from literature studies. The results show that although musyarakah contracts have great potential in realizing economic justice, their implementation still faces several obstacles, including operational complexity, risk management, and limited public understanding. This study finds that most musyarakah practices are in compliance with sharia principles, but still require improvements in aspects of risk sharing and loss management. The proposed development strategies include enhancing education, strengthening regulations, product innovation, and technology utilization. In conclusion, optimizing musyarakah contracts requires collaborative efforts from various stakeholders to overcome challenges and harness its potential in promoting fair partnership-based economic growth.